The Impact Of Product Knowledge And Brand Image On Purchasing Decisions Of Le Minerale In Surabaya - Thalib, Mochammad Rayyan; Wardani, Nuruni Ika Kusuma (UNIVERSITAS PAKUAN, 2025)
Environmental pollution caused by the accumulation of plastic waste, which is difficult to recycle, is a growing concern. Le Minerale offers bottled drinking water made from Polyethylene Terephthalate (PET), which, in addition to being free of BPA, is also highly recyclable. Furthermore, Le Minerale has been subjected to a black campaign from competitors in the market, particularly Aqua, the market leader in bottled water. This research seeks to investigate the effect of Product Knowledge and Brand Image on purchasing decisions for Le Minerale. A quantitative approach was used, employing an ordinal scale and Likert weighting technique, with a sample of 90 respondents. The study utilized a non-probability sampling method, specifically purposive sampling. Data analysis was conducted using the PLS (Partial Least Square) program. The results reveal that both product knowledge and brand image have a positive and significant influence on purchasing decisions for Le Minerale.